INTRODUCTION TO THE DIGITAL GENESIS OF EMERGING ADMINISTRATIVE PARADIGMS - Arcia-Hernández, Pedro; García-Manríquez, Mauricio Agustín; Torres-Vásquez, Jorge; Romero-Delgado, Hugo Eusebio; Espíritu-Martínez, Antony Paul; Gallegos-Gonzales, Orlando; Barboza-Zelada, Pedro Arturo; Pérez-Vargas, Reina Marlene; Casanueva-Yáñez, Galvarino (Journal of Posthumanism, 2025)
The purpose of this study is to investigate the main currents of the new administrative paradigms in the digital environment and their influence on the understanding and internalization of renewed management strategies in today's organizations. The specialized bibliographic research is articulated around three central axes: (a) Idea of paradigm according to the stages of knowledge (b) Idea of paradigm according to the development of administrative thought (c) Paradigmatic currents of administrative practices originated and generated in the digital era. The methodological design is aligned with the attributes of a Documented Reflection, being a referential work that uses bibliographic review, hermeneutics and the experience of the researcher as techniques. The results highlight that the nascent administrative paradigms are distinguished by their greater adaptability, horizontality and centrality in people. It was determined that the primary difference between classical administrative paradigms and those founded in the digital age lies in their notion of structure. That is, while conventional organizations tend to have hierarchical and centralized structures with defined levels of authority and responsibility, digital organizations adopt flatter and decentralized structures, driving agile decision-making and organizational flexibility.